GRAMMATICAL DEVIATION IN RICH BRIAN’S SONG LYRICS - Fisti Julianis Halawa; Sitasi Zagoto; Restu Damai Laia (Universitas Nias Raya, 2022)
This research aimed to analyze the types of grammatical deviation in Rich Brian’s song lyrics. This research is designed in qualitative research with descriptive approach. The data of this research is the three lyrics of Rich Brian’s songs, are: Dat stick, Who that be, and Glow like that. The prosecures used during analyzing the data were data condensation, data displayed, verifying and drawing conclusion (Miles, Huberman & Saldana 2014 31-32). Based on the data analysis, it was found that there were six types of grammatical deviation, there are omission, double negation, overgeneralization, deviation of preposition, deviation of verb and deviation of pronoun and the deviation was mostly occured in the lyrics of the songs is omission. The researcher suggests English teachers, student, and readers to use this research as the reference to increase their knowledge about grammatical deviation. Also the readers to use this research as a guidance in conducting the relevant research to sharpen and enlarge their literal development by trying to understand deviation in song lyrics.